PENERAPAN INOVASI PEMBUATAN IKAN LELE ASAP INTRODUKSI GAMBIR PADA POKLAHSAR RULE (RUMAH LELE) ATHALLAH - guttifera Guttifera; rizki eka puteri; siti lestari; maya resta kanya; Selly Ratna Sari (Jurnal Abdi Insani, 2023)
Rule Athallah has developed several processed fishery products, especially processed catfish-based products since 2017. Some of the superior products developed are smoked catfish, shredded catfish, let's go (ready-to-fry seasoned catfish), various crackers. The production and marketing process is carried out on an MSME scale and there has been no application of product development innovations to improve the quality of the products to be marketed. This activity aims to increase the value of smoked catfish products, increase the selling value of smoked catfish products produced by Poklahsar Rule Athallah so that the resulting products are able to reach a larger market. The activities carried out included counseling regarding the potential use of gambier in smoked catfish and hands-on training on making smoked catfish with the introduction of gambier. The material presented at the extension was followed by training on the role of gambier DNA production in fishery products. The partner of this activity is Poklahsar Rule Athallah. The implementation of activities is carried out offline, both counseling and direct training. Participants were given training on the procedure for selecting raw materials in the form of the right fresh fish, fish cutting techniques and lastly adding gambier to catfish before the smoking process was carried out. The series of service activities carried out is a solution to the problems faced by partners in increasing the value of products sold. The application of innovation in the form of the introduction of gambier in fishery products can directly increase the functional value of the resulting smoked catfish product. community service activities in the form of implementing innovations that can have an impact on sales which will later increase the income of members who are members of the Poklahsar Rule Athallah.